The Relationship between Self-Regulated Learning (SRL) and Cognitive Function with The Performance of qEEG Examination in First Year Medical Students - Dewi, Suzy Yusna; Digna, Audrey Alvura; Makkiyah, Feda Anisah; Pasiak, Taufiq Fredrik; Masiran, Ruziana` (Jurnal Psikiatri Surabaya, 2024)
Introductions: Medical students are required to lifelong learning.  Electroencephalog-raphy is a neuroscience tool that can be used to record brain wave activity related to a person's cognitive function. Objective: This study was conducted to see the relationship between self-regulated learning and cognitive function with quantitative electroencepha-logram (qEEG) parameters. Methods: This study used an observa-tional analytic approach to assess self-regulated learning and cog-nitive function using the MSLQ and MoCA-INA questionnaires. qEEG recording to see brain wave activity was done when the eyes were open and closed and seen in alpha and beta waves. The sam-ple of this study amounted to 32 respondents who were willing to carry out each research procedure.  Results: The study findings reveal a significant correlation between SRL and qEEG parameters. In the open-eye condition, such a correla-tion exists in the frontal and central regions with regard to alpha waves (P = 0.046 and P = 0.047). In contrast, in the closed-eye condition, it exists in the occipital, central, and parietal regions with alpha waves (P = 0.005, P = 0.021, and P = 0.049) and the central region with beta waves (P = 0.030). There is a significant correla-tion between cognitive function and qEEG parameters observed in both open and closed-eye conditions within the frontal region beta waves (P = 0.024, P = 0.044, and P = 0.021). Conclusions: There is a relationship between SRL and cognitive function with alpha and beta wave activity on qEEG recording.